2019
DOI: 10.1111/liv.14008
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLADPA1 and HLADPB1 polymorphisms with spontaneous HBsAg seroclearance in Caucasians

Abstract: Background & Aims Acute hepatitis B virus (HBV) infections may clear spontaneously or become chronic and run through different phases. The single nucleotide polymorphisms (SNPs) rs3077, rs9277535 and rs9277534 within the human leucocyte antigen (HLA)‐DP gene have been found to be associated with HBV susceptibility and persistence in Asians. However, evidence for the influence of these variants in Caucasians has been limited so far. The aim of our study was to investigate the impact of these polymorphisms on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…So, it may have a protective role against development of chronic HCV infection and deterioration of post-HCV liver cirrhosis. This comes in agreement with Koukoulioti et al [24] who found in their study that T allele may have a protective role.…”
Section: Discussionsupporting
confidence: 93%
“…So, it may have a protective role against development of chronic HCV infection and deterioration of post-HCV liver cirrhosis. This comes in agreement with Koukoulioti et al [24] who found in their study that T allele may have a protective role.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have found that genetic variants on the human leucocyte antigen (HLA)-DP gene are associated with HBsAg-seroclearance during the natural history of infection [ 64 ] or during treatment with NA [ 65 ], which seems to be consistent across different populations [ 66 ]. Other polymorphisms on genes linked to immunological function, such as the toll-like receptor 3 [ 67 ], interleukin 10 [ 68 ], and T-cell immunoglobulin and mucin domain-containing molecule 3 genes [ 69 ], have also shown to be linked to the natural progression of HBV infection and are less consistently studied [ 66 ].…”
Section: Determinants Of Functional Cure During Treated Hiv-hbv Co-infectionmentioning
confidence: 99%
“… 4 Thus, there is a strong link between HLA alleles and various diseases, including infections, autoimmune diseases, and tumors. 5 …”
Section: Introductionmentioning
confidence: 99%
“…The evolution of HLA molecular polymorphisms is thought to be the result of selection and adaptation via the modulation of host immunity against infections, tumors, and other diseases 4 . Thus, there is a strong link between HLA alleles and various diseases, including infections, autoimmune diseases, and tumors 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation